Real-time thermal expansion measurement system and the data acquisition and control application software - User interface - (:unkn) unknown (IEEE, 2003)
In order to operate the designed thermal expansion measurement system a user interface is constructed by using Borland Delphi This paper presents how the user interface is constructed and why it is necessary.